Yes, but Impossible: Implementation Research on the Acceptability of self-care practices among people affected by l eprosy in Rupandehi district, Nepal - Aryal, Pramila; Ahmad, Riris Andono; Utarini, Adi (BKM Public Health and Community Medicine, 2024)
Purpose: To explore the acceptability of self-care practices among people affected by leprosy and stakeholders in the Rupandehi district of Nepal. Methods: This qualitative study is based on in-depth interviews, key-informant interviews, and focus group discussions with the people affected by leprosy and stakeholders in Rupandehi district which is known to be a leprosy-endemic district in Nepal. Qualitative data was used to explore the acceptability of self-care practices and identify facilitators' barriers to accepting self-care practices. A total of 28 respondents were interviewed. Thematic analysis was used to interpret the data based on a TFA framework. Results: Leprosy-affected people have accepted the self-care practices and have a positive attitude towards it. However, due to poverty, lack of resources, and availability of time they find it impossible to practice self-care. To make it worse, less priority was given by the government sector to support self-care practices. Improving perception, minimizing stigma and taboos regarding self-care practices as well as improving service providers' attitudes and support from nongovernmental organizations were identified as facilitators. Conclusion: Despite the awareness and acceptance, self-care is not yet practiced. The program implementor should focus on the availability of resources and policy for poverty reduction